Upaya Deteksi Dini Osteoarthritis pada Karyawan Universitas Tarumanagara dengan Instrumen WOMAC - Tjie Haming Setiadi; Noer Saelan Tadjudin; Alexander Halim Santoso; Susy Olivia Lontoh (BADAN PENERBIT STIEPARI PRESS, 2025)
Osteoarthritis (OA) is a degenerative joint disease that commonly affects individuals in their productive and elderly years, significantly impairing quality of life. Early detection is essential to prevent disability due to OA, particularly in vulnerable groups such as university employees. This community service activity involved OA screening of 26 employees at Tarumanagara University using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). In addition to screening, participants received education on risk factors and OA prevention. The screening revealed varied levels of joint pain, stiffness, and functional limitations. The average WOMAC score was 32.27 (SD 17.63), ranging from 4 to 66 points. Several participants exhibited moderate to severe symptoms, especially during activities such as climbing stairs and performing household tasks. The WOMAC instrument proved effective in detecting early functional joint complaints. The educational component played a crucial role in raising participants’ awareness of the importance of healthy lifestyles and early OA management. This initiative successfully identified OA risks among university employees and enhanced their knowledge regarding disease prevention. Early detection and education should be established as routine workplace health programs. Keywords: Early Detection, Community Service, Osteoarthritis, University Employees, WOMAC